2019
DOI: 10.1007/978-3-030-22566-7_64
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Non-proprietary UHPC for Use in Rehabilitation/Strengthening Applications

Abstract: UHPFRC has become one of the most promising cement-based materials for the next generation of infrastructures because of its good workability, outstanding mechanical properties, and excellent durability. A promising field of application is the rehabilitation and/or strengthening of existing reinforced concrete structures, in which a new layer of UHPFRC replaces the deteriorated concrete (cracked, carbonated, chloride attack, etc.). The combination of the UHPFRC as protective layer, which can be reinforced, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…To date, much research into this material has analysed its mechanical properties, and only a few studies on its microstructure or durability have been published. All the authors have observed lower porosity and water and gas permeability than in conventional concrete [ 36 , 37 , 38 , 39 , 40 ]. However, discrepancies have been identified in reported findings, due to their dependence on many factors, including type of additions and nanoparticles used [ 23 , 35 , 41 ] and curing conditions [ 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, much research into this material has analysed its mechanical properties, and only a few studies on its microstructure or durability have been published. All the authors have observed lower porosity and water and gas permeability than in conventional concrete [ 36 , 37 , 38 , 39 , 40 ]. However, discrepancies have been identified in reported findings, due to their dependence on many factors, including type of additions and nanoparticles used [ 23 , 35 , 41 ] and curing conditions [ 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…In CONSTRUCT-LABEST, research projects have been conducted to make UHPFRC a more practical, cost-effective, eco-efficient, and widely accepted material/solution. One of the aims was to develop a UHPFRC using locally available raw materials, incorporating local non-value-added by-products or waste materials and simple manufacturing and curing methods [53][54][55]. Those features can reduce the cost and ecological footprint of UHPFRC and contribute to a circular economy.…”
Section: Research Significance and Objectivesmentioning
confidence: 99%
“…The author developed the UHPFRC [53][54][55] using locally available materials in Portugal/Europe. The mixture design included a local waste material, the spent equilibrium catalyst (ECat) from the fluid catalytic cracking unit of Sines Refinery in Portugal.…”
Section: Raw Materials and MIX Designmentioning
confidence: 99%
“…For this reason, only limestone fine aggregate (not quartz) was used in this study. Several studies have reported using limestone powder [13,14,26] and coarse and fine limestone aggregates for developing nonproprietary UHPC mixes [27][28][29] with varying degrees of success. The results from this research would extend to other locations where only limestone fine aggregate is available.…”
Section: Background and Significant Of Studymentioning
confidence: 99%
“…For this reason, many different investigations have been conducted to develop non-proprietary UHPC mixtures, typically achieving close to the same mechanical properties of commercially available UHPC but with significantly lower cost. Several researchers developed the non-proprietary UHPC with locally available materials in different locations and could reach the minimum requirements for UHPC mixtures [12][13][14]. Several studies also studied their developed non-proprietary UHPC mixture in different applications like connecting precast deck panels in retrofit jobs [15].…”
Section: Introductionmentioning
confidence: 99%